Analisa Instalasi Pengolahan Air Terhadap Pemakaian Tawas dan Kualitas Air Produksi - Muhammad Ryan Nur Rochim; Firra Rosiariawari (Yayasan Literasi Sains Indonesia, 2023)
Water is an important factor in determining the needs of mankind on earth, the existence of water is very much and very abundant on earth, for example springs, reservoirs, rivers, lakes, to the sea. As we all know, the area of waters on earth is larger than the existing land area, so that the water problem is the main problem, both the problem of clean water supply, water pollution, and the problem of water pollution and distribution. In order for IPA to operate properly, it is necessary to evaluate IPA. This study aims to: 1) Know the use of alum in PDAM xyz; 2) Comparing the quality of production water produced with the PERMENKES No. standard. 492 in 2010; 3) Know how the process of water treatment; the data used or obtained from PDAM is data on the use of alum and checking the physical and chemical parameters, the physical and chemical parameters used include turbidity, pH, temperature, color and odor. According to the results obtained, the tested parameters met the PERMENKES No. standards. 492 of 2010. The water treatment process is Intake, Clarifier which consists of several processes, then there is a reservoir. The source of water used in the water treatment plant is using the Brantas River, the Brantas River itself is included in group 3. The use of alum that is too large is due to the absence of a pre-sedimentation unit.